2010
DOI: 10.1111/j.1439-0272.2009.01002.x
|View full text |Cite
|
Sign up to set email alerts
|

TUNEL assay and SCSA determine different aspects of sperm DNA damage

Abstract: For the determination of sperm DNA damage, different assays are used. However, no further distinction is made and the literature generally speaks about DNA damage. Thus, this study aimed at comparing the sperm chromatin structure assay (SCSA) and the TUNEL assay. In 79 patients, sperm DNA damage was determined flow cytometrically using the SCSA and the TUNEL assay. Moreover, normal sperm morphology was evaluated according to strict criteria. A statistical comparison of the two methods was performed using stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 52 publications
1
67
0
2
Order By: Relevance
“…A high correlation between SCSA and TUNEL results ( r = 0.859; p < 0.01) has also been reported by Gorczyca et al [153]. In contrast, Henkel et al could not corroborate the aforesaid findings and concluded that the assays were not comparable [154]. Our own data on TUNEL and SCD to measure sperm DNA fragmentation in a population of men with UI showed that the methods were poorly correlated ( r = 0.28) [127].…”
Section: Clinical Utility Of Sperm Functional Tests In Unexplained Masupporting
confidence: 59%
“…A high correlation between SCSA and TUNEL results ( r = 0.859; p < 0.01) has also been reported by Gorczyca et al [153]. In contrast, Henkel et al could not corroborate the aforesaid findings and concluded that the assays were not comparable [154]. Our own data on TUNEL and SCD to measure sperm DNA fragmentation in a population of men with UI showed that the methods were poorly correlated ( r = 0.28) [127].…”
Section: Clinical Utility Of Sperm Functional Tests In Unexplained Masupporting
confidence: 59%
“…A negative correlation between sperm DNA damage and quality of embryo, development of blastocyst, implantation rate has been found in men opting for ICSI when the DNA damage was assessed by ISNT and TUNEL [91][92][93][94].…”
Section: Clinical Aspects and Relevance Of Dna Integrity Testsmentioning
confidence: 99%
“…(Alvarez, 2005;Henkel, 2007). The TUNEL and SCSA assays correlate well (Evenson et al, 2007), although they determine different aspects of sperm function (Henkel et al, 2010;Mitchell et al, 2011).…”
Section: The Tunel Assaymentioning
confidence: 99%